Un-explained visual loss following silicone oil removal: Results of the Pan American Collaborative Retina Study (PACORES) Group (2017)
Purpose: To report the incidence and clinical features of patients that experienced un-explained visual loss following silicone oil (SO) removal. Methods: Multicenter retrospective study of patients that underwent SO removal during 2000-2012. Visual loss of ≥2 lines was considered significant. Results: A total of 324 eyes of 324 patients underwent SO removal during the study period. Forty two (13%) eyes suffered a significant visual loss following SO removal. Twenty three (7.1%) of these eyes lost vision secondary to known causes. In the remaining 19 (5.9%) eyes, the loss of vision was not explained by any other pathology. Eleven of these 19 patients (57.9%) were male. The mean age of this group was 49.2 ± 16.4 years. Eyes that had an un-explained visual loss had a mean IOP while the eye was filled with SO of 19.6 ± 6.9 mm Hg. The length of time that the eye was filled with SO was 14.8 ± 4.4 months. In comparison, eyes that did not experience visual loss had a mean IOP of 14 ± 7.3 mm Hg (p < 0.0002) and a mean tamponade duration of 9.3 ± 10.9 months (p < 0.0001). Conclusions: An un-explained visual loss after SO removal was observed in 5.9% of eyes. Factors associated with this phenomenon included a higher IOP and longer SO tamponade duration. © The Author(s) 2017.